2006
DOI: 10.1210/en.2005-1286
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hepatic Expression of the High-Density Lipoprotein Receptor SR-BI on Lipoprotein Metabolism and Female Fertility

Abstract: The etiology of human female infertility is often uncertain. The sterility of high-density lipoprotein (HDL) receptor-negative (SR-BI(-/-)) female mice suggests a link between female infertility and abnormal lipoprotein metabolism. SR-BI(-/-) mice exhibit elevated plasma total cholesterol [with normal-sized and abnormally large HDL and high unesterified to total plasma cholesterol (UC:TC) ratio]. We explored the influence of hepatic SR-BI on female fertility by inducing hepatic SR-BI expression in SR-BI(-/-) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
78
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 92 publications
3
78
1
4
Order By: Relevance
“…1 ). This is in contrast to work previously published by Yesilaltay et al ( 69 ), which found overexpression of LCAT in mice on a Scarab ( Ϫ / Ϫ ) background was not able to normalize the FC/TC ratio. The differences between our results and theirs are likely due to the much greater increase in LCAT expression in our mice compared with the previous study ( 31,70 ).…”
Section: Discussioncontrasting
confidence: 99%
“…1 ). This is in contrast to work previously published by Yesilaltay et al ( 69 ), which found overexpression of LCAT in mice on a Scarab ( Ϫ / Ϫ ) background was not able to normalize the FC/TC ratio. The differences between our results and theirs are likely due to the much greater increase in LCAT expression in our mice compared with the previous study ( 31,70 ).…”
Section: Discussioncontrasting
confidence: 99%
“…Studies in the mouse demonstrate the importance of HDL integrity for oocyte competence; as knockout mice lacking the HDL receptor scavenger receptor class B, member 1 (SRBI) are infertile due to fertilised oocytes arresting before the morula stage (Miettinen et al 2001). These mice have abnormally large circulating HDL particles and, interestingly, restoration of SRBI expression in the liver alone is sufficient to normalise HDL particle size and restore fertility (Yesilaltay et al 2006). Increased HDL in human follicular fluid was associated with low embryo fragmentation (Browne et al 2008(Browne et al , 2009, suggesting that HDL components play a cytoprotective role for the oocyte.…”
Section: Fatty Acid Supply To the Cocmentioning
confidence: 99%
“…The observation that nonviable oocytes are produced has led to the implication that the ovulatory process itself is disrupted in some way ( 11,12 ). Although mechanisms remain unclear, it is intriguing that targeted overexpression of SCARB1 in the liver rescues fertility of SCARB1 null mice to nearly the levels found in wild-type mice ( 13 ). In addition, fertility was rescued by treatment with Probucol, a drug that lowers circulating cholesterol independent of SCARB1 ( 14 ).…”
Section: Rna and Protein Analysismentioning
confidence: 99%